ACOEM OEM Core Competencies: 2021. Issue 7 (July 2021) - Hartenbaum, Natalie P.; Baker, Beth A.; Levin, Jeffrey L.; Saito, Kenji; Sayeed, Yusef; Green-McKenzie, Judith
Abstract : N/A: Competency is defined as possession of sufficient physical, intellectual, and behavioral qualifications to perform a task or serve in a role which adequately accomplishes a desired outcome. Recognizing the need for defining competencies essential to occupational and environmental medicine (OEM) physicians, the American College of Occupational and Environmental Medicine developed its first set of OEM Competencies in 1998. Later updated in 2008, and again in 2014, the increasing globalization and modernization of the workplace, along with published research on OEM practice, required an update to ensure OEM physicians stay current with the field and practice of OEM. Delineation of core competencies for the profession provides employers, government agencies, health care organizations, and other health practitioners a solid context of the role and expertise of OEM physicians.